Transparency of Assessment in Practice Environments. An extension of the TAPE Model - Stone, Clare (The Journal of Practice Teaching and Learning, 2019)
Following research into UK social work students’ experiences of assessment, ‘Author’ (2018) concluded that not all students appeared to be aware of who contributed towards their assessment nor what constituted reasonable assessment practice. The Transparency of Assessment in Practice Education (TAPE) Model was offered to the practice learning community as a tool to engage academics, practice educators and students in dialogue about assessment during placements. The purpose of the TAPE model is for all stakeholders to explore expectations to avoid misunderstandings and ambiguity about assessment. This article explores the potential use of the model within wider contexts of learning and assessment including the assessment of the users of services. The wider application of this innovative model suggests a name change to Transparency of Assessment in Practice Environments.